HU of Streptococcus pneumoniae Is Essential for the Preservation of DNA Supercoiling - Ferrándiz, María-José; Carreño, David; Ayora, Silvia; de la Campa, Adela G. (Frontiers in Microbiology, 2018)
The histone-like protein HU is a conserved nucleoid-associated protein that is involved in the maintenance of the bacterial chromosome architecture. It is the only known nucleoid-associated protein in Streptococcus pneumoniae, but it has not been studied. The pneumococcal gene encoding this protein, hlp, is shown herein to be essential for cell viability. Its disruption was only possible either when it was duplicated in the chromosome and its expression induced from the PZn promoter, or when hlp was cloned into a plasmid under the control of the inducible Pmal promoter. In vitro assays indicated that pneumococcal HU shows a preference for binding to supercoiled DNA rather than to linear or nicked DNA. In vivo experiments in which the amount of HU was manipulated showed a relationship between the amount of HU and the level of DNA supercoiling. A two-fold reduction in the amount of HU triggered a 21% increase in DNA relaxation in untreated cells. However, in cells treated with novobiocin, a drug that relaxes DNA by inhibiting DNA gyrase, a 35% increase in DNA relaxation was observed, instead of the expected 20% in cells with a constitutive HU amount. Conversely, a four-fold HU increase caused only 14% of DNA relaxation in the presence of novobiocin. Taken together, these results support an essential role for HU in the maintenance of DNA supercoiling in S. pneumoniae.